Micro-Ribonucleic Acid Profiles From Microarray in Ankylosing Spondylitis - Hye-Mi JIN; Young-Nan CHO; Seung-Jung KEE; Shin-Seok LEE; Yong-Wook PARK; Tae-Jong KIM (Archives of Rheumatology, 2016)
Objectives: This study aims to detect candidate micro-ribonucleic acids (miRNAs) from microarray within peripheral blood mononuclear cells and synovial fluid mononuclear cells in patients with ankylosing spondylitis (AS). Patients and methods: Samples from three AS patients (3 males, mean age 37.3±2.5 years; range 35 to 40 years) and three healthy controls (3 males, mean age 39.0±2.6 years; range 37 to 42 years) were obtained for miRNA microarray. The microarray experiment proceeded only when the quality of total RNAs were considered to have “passed”, and their integrity was good by total RNA quality control using Agilent Bioanalyzer 2100. Hierarchical clustering was performed to understand the impact of the storage condition on the miRNA expression profiles. MiScript primer assays were used for semiquantitative determination of the expression of human miRNAs to validate results from miRNA microarray. Results: A total of 887 miRNAs were screened by microarray among groups. After normalization of the raw data, we noted that the expression of five miRNAs was significantly lower (fold change ≤0.5 and p≤0.05) and only hsa-miR-424-5p was significantly higher in AS peripheral blood mononuclear cell (fold change ≥2 and p≤0.05). In AS synovial fluid mononuclear cells, we identified that expressions of 16 miRNAs were significantly down regulated whereas only hsa-miR-424-5p was significantly upregulated (fold change ≥2 and p≤0.05). All above-mentioned miRNAs were reevaluated for further validation. Finally, significantly increased hsa-miR-424-5p and decreased hsa-miR-377 were found in synovial fluid mononuclear cells from AS patients compared with healthy controls. Based on target prediction programs and published papers, potential target genes and its pathways were screened. Conclusion: miR-424-5p was increased and miR-377 was decreased in synovial fluid mononuclear cells from patients with AS. These two miRs might have functional roles in patients with arthritis via different pathways.